Improving Biology Learning Outcomes through Guided Inquiry with Video Media - Megahati S, Ruth Rize Paas (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
Lack of student participation during discussions causes students to become inactive when learning, and difficulty in answering teacher questions because the information the teacher conveys is not understood by students. This results in student scores still below the KKM in Global warming is one of them. The minimum completeness criteria set at SMPN 2 Lembah Gumanti is 65. The purpose of the study was to determine the effect of the application of the guided inquiry model with video media on the biology learning outcomes of seventh-grade students of SMPN 2 Lembah Gumanti, Solok Regency. The type of research is an experiment with a research design Randomized Control Group Posttest Only Design. The use of t-test is used in the affective domain as a data analysis technique and the t-test was used in the cognitive and psychomotor domains for data analysis techniques. 1 the experimental class has an average score of 62.38 with a predicate of C (Enough) while the control class has an average value of 53.22 with a predicate of D (Less). Hypothesis test 0.05 obtained t-count 2.90 > t-table 1.67, meaning that H1 is accepted. The guided inquiry learning model accompanied by video media can improve the biology learning outcomes of class VII students of SMPN 2 Lembah Gumanti, Solok Regency.